2017
DOI: 10.2527/jas2017.1732
|View full text |Cite
|
Sign up to set email alerts
|

Narasin effects on energy, nutrient, and fiber digestibility in corn-soybean meal or corn-soybean meal-dried distillers grains with solubles diets fed to 16-, 92-, and 141-kg pigs

Abstract: Three experiments were conducted to determine the effect of narasin on growth performance and on GE and nutrient digestibility in nursery, grower, and finishing pigs fed either a corn-soybean meal (CSBM) diet or a CSBM diet supplemented with distillers dried grains with solubles (DDGS), in combination with either 0 or 30 mg narasin/kg of diet. In Exp. 1 (64 gilts, initial BW = 9.0 kg, SD = 1.0 kg) and Exp. 2 (60 gilts. initial BW = 81.1 kg, SD = 6.1 kg), gilts were allotted into individual pens and fed their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…This is not surprising given that characterization of manure bacteria and composition in a complex matrix (Cotta et al, 2003;Trabue et al 2016b) and the selection of the manure storage tank and length of storage (Trabue et al 2016a) can have profound effects on the data obtained making interpretation of the results challenging. In the current experiment, narasin had minimal effect on manure composition (Table 2) and this is supported by Kerr et al (2017) who, using the same pigs, reported that energy or nutrient digestibility in finishing pigs was unaffected by narasin supplementation. The greater amount of manure nutrients as a percentage of animal intakes due to narasin supplementation (Table 3) is best understood from the perspective that narasin inhibits gross biomass functions as seen in lower degradation rates of total and volatile solids of manure treated with and without narasin (Andersen and Regan, 2014), but some more specific functions are unaffected and this difference may be due in part to the level of functional redundancy for that particular function.…”
Section: Manure Characteristics and Total Manure Nutrient Outputsupporting
confidence: 79%
See 2 more Smart Citations
“…This is not surprising given that characterization of manure bacteria and composition in a complex matrix (Cotta et al, 2003;Trabue et al 2016b) and the selection of the manure storage tank and length of storage (Trabue et al 2016a) can have profound effects on the data obtained making interpretation of the results challenging. In the current experiment, narasin had minimal effect on manure composition (Table 2) and this is supported by Kerr et al (2017) who, using the same pigs, reported that energy or nutrient digestibility in finishing pigs was unaffected by narasin supplementation. The greater amount of manure nutrients as a percentage of animal intakes due to narasin supplementation (Table 3) is best understood from the perspective that narasin inhibits gross biomass functions as seen in lower degradation rates of total and volatile solids of manure treated with and without narasin (Andersen and Regan, 2014), but some more specific functions are unaffected and this difference may be due in part to the level of functional redundancy for that particular function.…”
Section: Manure Characteristics and Total Manure Nutrient Outputsupporting
confidence: 79%
“…After manure sampling, the manure in the tanks was dumped and the tanks cleaned for the second group of pigs. Additional detail on the effects of diet and narasin on energy, nutrient, mineral, and fiber digestibility are presented elsewhere (Kerr et al, 2017).…”
Section: Diets and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by previously published research on diet particle size and pig performance (Hancock & Behnke, 2001; Liu, Souza, Baidoo, & Shurson, 2012). The current data are also in agreement with others (Kerr, Ziemer, Trabue, Crouse, & Parkin, 2006, 2015, 2017, 2018; Trabue & Kerr, 2014), indicating that if diets with a moderate amount of fiber are balanced for energy, pigs will perform comparably to pigs fed a low‐fiber diet.…”
Section: Discussionsupporting
confidence: 92%
“…This, however, was not noted in the current trial, where the S content of manures from DDGS and CSBM diets were both approximately 0.094 g L −1 and where SH contained only 0.07 g S L −1 . The impact of diet particle size on manure composition has not been thoroughly studied, but it would be assumed that any diet composition or diet processing method that increased nutrient digestibility by an animal would increase nutrient retention, thereby reducing its “input” in the manure storage system (Kerr, Trabue, & Andersen, 2017, 2018). As reported in pigs fed the same diets as used in the current study (Saqui‐Salces, Luo, Urriola, Kerr, & Shurson, 2017), decreasing particle size resulted in an increase in the digestibility of DM (used as a surrogate for C), and N and S, which, in the data reported herein, corresponded to a decrease in manure NH 4 –N, C, and N but not manure sulfide or S.…”
Section: Discussionmentioning
confidence: 99%